2023
DOI: 10.1007/s00214-023-03041-5
|View full text |Cite
|
Sign up to set email alerts
|

Yttrium decorated fullerene C30 as potential hydrogen storage material: Perspectives from DFT simulations

Debolina Paul,
Pratap Mane,
Utpal Sarkar
et al.

Abstract: Using the density functional theory method, hydrogen storage capacity for Yttrium doped fullerene has been studied. Bonding of Y atom with that of C 30 is due to the charge transfer taking place from the dorbital of the Y atom to the 2p-orbital of the C atom of C 30 . It has been predicted that a single Y atom can adsorb 7 hydrogen molecules, whose binding energy falls within the range as suggested by the U.S. Department of Energy (DOE). Interaction of hydrogen on the metal is because of the Kubas interaction … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 87 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…65,66 C 30 when decorated with Y could hold seven hydrogen molecules with an average binding energy of −0.385. 67 When C 30 is bound to the graphene layer, the Ti atom on it could hold H 2 with a binding energy of −1.41 eV. 68 Though studies are reported on C 30 , no studies have been performed on Ti decorated C 30 .…”
Section: Introductionmentioning
confidence: 99%
“…65,66 C 30 when decorated with Y could hold seven hydrogen molecules with an average binding energy of −0.385. 67 When C 30 is bound to the graphene layer, the Ti atom on it could hold H 2 with a binding energy of −1.41 eV. 68 Though studies are reported on C 30 , no studies have been performed on Ti decorated C 30 .…”
Section: Introductionmentioning
confidence: 99%